The Agreement between Feline Pancreatic Lipase Immunoreactivity and DGGR-Lipase Assay in Cats—Preliminary Results - Magdalena Maria Krasztel (MDPI AG, 2021)
The colorimetric catalytic assay based on the use of 1,2-o-dilauryl-rac-glycero-3-glutaric acid-(6′-methylresorufin) (DGGR) ester as a substrate for pancreatic lipase activity is commonly used for the diagnosis of pancreatitis in dogs and cats. Even though the assay has generally been shown to yield consistent results with feline pancreatic lipase immunoreactivity (fPLI) assay, the agreement may vary between assays of different manufacturers. In this study, the chance-corrected agreement between a DGGR-lipase assay offered by one of the biggest providers of diagnostic solutions in Poland and fPLI assay was investigated. The study was carried out on 50 cats in which DGGR-lipase activity and fPLI were tested in the same blood sample. The chance-corrected agreement was determined using Gwet’s AC1 coefficient separately for the fPLI assay’s cut-off values of >3.5 μg/L and >5.3 μg/L. The DGGR-lipase activity significantly positively correlated with fPLI (Rs = 0.665; CI 95%: 0.451, 0.807, p < 0.001). The chance-corrected agreement between the fPLI assay and DGGR-lipase assay differed considerably depending on the cut-off values of the DGGR-lipase assay. When the cut-off value reported in the literature (>26 U/L) was used, it was poor to fair. It was moderate at the cut-off value recommended by the laboratory (>45 U/L), and good at the cut-off value recommended by the assay’s manufacturer (>60 U/L). The highest agreement was obtained between the fPLI assay at the cut-off value of 3.5 μg/L and the DGGR-lipase assay at the cut-off value of 55 U/L (AC1 = 0.725; CI 95%: 0.537, 0.914) and between the fPLI assay at the cut-off value of 5.3 μg/L and the DGGR-lipase assay at the cut-off value of 70 U/L (AC1 = 0.749; CI 95%: 0.577, 0.921). The study confirms that the chance-corrected agreement between the two assays is good. Prospective studies comparing both assays to a diagnostic gold standard are needed to determine which of them is more accurate.